Exploring farmer and advisor lameness management behaviors using the COM-B model of behavior change - Clark, Beth; Proctor, Amy; Mahon, Niamh; Holloway, Lewis (Frontiers in Veterinary Science, 2024)
This paper applies the COM-B framework to farmer and farm advisor understandings and responses to lameness in sheep, beef, and dairy systems. It reflects on how farmers' and advisors' capability, opportunity, and motivation (COM-B) influence lameness management practices in these farming systems, and considers the interaction between these three factors, and stakeholders' behaviour.Interviews with 29 farmers and 21 farm advisors in the north of England were conducted. Thematic analysis was undertaken with results categorised in relation to the COM-B framework focusing on barriers and enablers of lameness management. Use of the COM-B model provides a useful means of understanding the underlying behavioural mechanisms that contribute towards the persistence of lameness. This includes the complexities and interactions which hamper implementation of lameness management best practice. The findings highlight three key areas to address with interventions to improve lameness management on farm: 1) removing physical and social barriers for lameness management; 2) improving psychological capability and motivation for lameness management; and 3) facilitating relationships and developing communication between farmers and advisors.In particular, the value of exploring both farmer and advisor perspectives on behaviour in the animal health context is demonstrated. Future interventions should look to target these three areas to overcome barriers and focus on factors that enable positive lameness practices to occur.